2019
DOI: 10.3390/cells8111315
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Redox-Balance Involvement in Temozolomide Resistance-Related Molecular Mechanisms in Glioblastoma

Abstract: Glioblastoma (GBM) is the most common astrocytic-derived brain tumor in adults, characterized by a poor prognosis mainly due to the resistance to the available therapy. The study of mitochondria-derived oxidative stress, and of the biological events that orbit around it, might help in the comprehension of the molecular mechanisms at the base of GBM responsiveness to Temozolomide (TMZ). Sensitive and resistant GBM cells were used to test the role of mitochondrial ROS release in TMZ-resistance. Chaperone-Mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 38 publications
(52 reference statements)
4
40
0
Order By: Relevance
“…In our experiment, high‐glucose stimulation attenuated proliferation and migration while enhanced oxidative stress in mice skin fibroblasts, which was most serious in that from SIRT3 knockout mice. On the other hand, mitochondria provided a place for ROS generation, and the structural destruction or functional dysfunction was prone to destroy the homeostasis to induce oxidative damage . Indeed, we confirmed that SIRT3 KO mice did have above abnormal manifestations on ultrastructure and mitochondrial membrane potential.…”
Section: Discussionsupporting
confidence: 73%
“…In our experiment, high‐glucose stimulation attenuated proliferation and migration while enhanced oxidative stress in mice skin fibroblasts, which was most serious in that from SIRT3 knockout mice. On the other hand, mitochondria provided a place for ROS generation, and the structural destruction or functional dysfunction was prone to destroy the homeostasis to induce oxidative damage . Indeed, we confirmed that SIRT3 KO mice did have above abnormal manifestations on ultrastructure and mitochondrial membrane potential.…”
Section: Discussionsupporting
confidence: 73%
“…The iron-dependent accumulation of ROS is the characteristic of ferroptosis (54). Furthermore, ROS-induced lipid peroxidation is not only a critical role in ferroptosis, but also affects the apoptosis, autophagy, and TMZ resistance in glioma cells (53,55,56). Biochemically, the intracellular GSH depletion, which inhibits anti-peroxidant defense and iron, involved in the Fenton reaction would result to the accumulation of lipid peroxidation, promoting ferroptosis.…”
Section: Ros In Ferroptosis and Tmz Resistancementioning
confidence: 99%
“…Recently published research data identi ed the contribution of GBM cells to the up-regulation of LAMP-2A and CMA activity in pericytes through cell-cell interaction, which ablated pericytes antitumor immune function essential for GBM survival [12]. However, in terms of temozolomide (TMZ) treatment, in vitro studies showed CMA mediated downregulation of HIF-1α improved the response of TMZ-resistant GBM cells, and blocking CMA induced resistance of TMZ-sensitive cells [13,14]. While in breast cancer inhibiting CMA by downregulating LAMP-2A could augment sensitivity to doxorubicin [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recent published papers identi ed the role of LAMP-2A in modulating GBM-pericytes interaction and temozolomide resistance via CMA [12][13][14]. However, the intrinsic function of LAMP-2A and CMA in GBM development and progression has been poorly elucidated.…”
Section: Introductionmentioning
confidence: 99%